Comparative Antifungal Efficacy of Ketoconazole and Nystatin on Chlamydospore Production in Candida albicans Isolated from Oral Lesions in Cancer Patients (مجلة الرازي الطبية, 2025)
Candida albicans threatens immunocompromised patients, partly via chlamydospores—dormant, stress-tolerant forms. Reducing these structures may limit persistence and relapse. We compared nystatin (polyenic membrane binder) versus ketoconazole (azole ergosterol-synthesis inhibitor) for suppressing chlamydospore production by C. albicans from cancer-patient oral lesions. Twenty isolates were cultured on cornmeal agar + 1% Tween-80 and exposed to nystatin or ketoconazole at 0.5–10 µg/mL. After 24–48 h at 30 °C, chlamydospores were stained and counted microscopically (spores/10 HPF). ANOVA with Tukey post-hoc tested drug, concentration, and interaction (p